An Information System for Vocational Decisions (ISVD) Cultivating the Possibility for Career Through Operations - Tiedeman, David V.; Harvard Univ., Cambridge, MA. Graduate School of Education ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1966)
A major thesis is propounded: The acquisition of the vocational role in life can be considerably improved by further incorporating vocational education and development into liberal education. The work of Ashcraft on career development and curriculum and that of Crites on vocational maturation are cited and provide the backdrop against which the author lays out the Information System for Vocational Decisions (ISVD). This prototypic, computer-based system represents a deliberate effort to cultivate vocational maturation, i.e., to make it occur. ISVD is discussed in the following aspects: (1) its general framework; (2) its data bases; (3) its decision-making paradigm; (4) its computer routines; and (5) materials. The status and prospects of the system as of December, 1966 are elaborated. (TL)
Sponsoring Agency: Office of Education (DHEW), Washington, DC.
Contract Number: OEG-1-6-061819-2240.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Career Choice; Career Counseling; Career Development; Career Planning; Computers; Educational Innovation; Educational Technology; Guidance Programs; Information Systems; Man Machine Systems; School Counseling; Information System for Vocational Decisions